Effect of topical antimicrobial treatment on aerobic bacteria in the stratum corneum of human skin. - Hendley, J O (1991)
The efficacy of antimicrobial agents applied topically to the skin surface in eradicating coagulase-negative staphylococci (CNS) residing in the stratum corneum underlying the surface was examined. Glabrous skin was sampled with a 26-cm2 contact plate containing Trypticase soy agar. Five antiseptic solutions and four antimicrobial ointments were evaluated. The antiseptic solutions (10% povidone-iodine, 2% aqueous iodine, 2% tincture of iodine, 70% ethanol, and 0.5% chlorhexidine-ethanol) were applied for 15 s with a gauze sponge. The antimicrobial ointments (iodophor, silver sulfadiazine, mupirocin, and a triple-antibiotic ointment containing neomycin, polymyxin, and bacitracin) were applied and covered for 6 h with gauze. After treatment, the surface was sampled, 15 to 25 keratinized layers were subsequently removed by sequential stripping with cellophane tape, and the stratum corneum was sampled. All agents were effective in eradicating CNS from the surface (80 of 88 trials). However, only 2% iodine (17 of 20 trials), iodophor (8 of 12), mupirocin (6 of 10), and the triple-antibiotic ointment (9 of 11) eradicated CNS from the stratum corneum reliably (greater than or equal to 50% of trials). The stratum corneum was repopulated with resident flora within 24 h of treatment with 2% iodine (4 of 4 trials), iodophor (6 of 7), or mupirocin (5 of 6), but repopulation occurred in only 1 of 7 trials with the triple-antibiotic ointment. Topical treatment of skin with antimicrobial agents usually eradicates CNS from the skin surface but may not eradicate CNS from the stratum corneum. Only the triple-antibiotic ointment eradicated CNS from the stratum corneum and prevented repopulation with resident flora.